Integrated CAD by Optimization: Architecture, Engineering, Construction, Urban Development and Management - Chakrabarty, B. K (Springer International Publishing AG, 2022)
This book presents range of topics concerning integrated CAD (including Optimization) for use in Architecture (including Planning), Civil Engineering and Construction (AEC), and thus, helps introduce a full-length treatment of the subject, enabling practitioners to adopt an Integrated Computer-Aided Design Approach in their professional activity.